Intramolecular cyclopropanation of epichlorohydrin-derived unsaturated chlorohydrins - Hodgson, D; Chung, Y; Paris, J (2005)
Concise stereoselective syntheses of bicyclo[3.1.0]hexan-2-ols and a bicyclo[4.1.0]heptan-2-ol are achieved via regioselective ring-opening of epichlorohydrin with allylic and homoallylic Grignard reagents, followed by lithium 2,2,6,6-tetramethylpiperidide-induced intramolecular cyclopropanation of the resulting unsaturated chlorohydrins. © Georg Thieme Verlag Stuttgart.